Investigating the Dimensionality of Psychological Contract from a Spiritual Perspective: an Empirical Study of Indonesian Employees - Suhartini, Tien (Indonesian Journal of Islamic Literature and Muslim Society, 2022)
Based on the Western value system, research on the psychological contract has received immense attention from human resources management researchers.  However, psychological contract from the spiritual perspective has not been much explored. This empirical study attempts to enrich the understanding of the psychological contract phenomenon from a spiritual perspective. This is a research paper to explore the dimensionalities of a spiritual psychological contract with examined both inner (structure) and outer (measurement) models via Partial least squares structural equation modeling (PLS-SEM). A survey of 108 employees in business organizations in Indonesia, Malaysia, the United Kingdom, and Taiwan was drawn for the study using a nonprobability convenience sampling procedure to obtain a more representative sample. The construct validity of the spiritual psychological contract (SPC) via SmartPLS 3.2.7 software led to the major finding; the SPC measurement model in the business organizational context is explained by three components i.e., transactional, relational, and liturgical contract. This is a new insight into psychological contract research and needs further studies to explore it.